A dietary pattern rich in calcium, potassium, and protein is associated with tibia bone mineral content and strength in young adults entering initial military training. Issue 1 (5th January 2019) - Nakayama, Anna T; Lutz, Laura J; Hruby, Adela; Karl, James P; McClung, James P; Gaffney-Stomberg, Erin
ABSTRACT: Background: Stress fracture risk is elevated during initial military training (IMT), particularly in lower-extremity bones such as the tibia. Although the etiology of stress fractures is multifactorial, lower bone strength increases risk. Objective: The objective of this study was to assess, through the use of peripheral quantitative computed tomography, whether adherence to a dietary pattern rich in calcium, potassium, and protein before IMT is positively associated with bone indexes in young adults entering IMT. Design: A cross-sectional analysis was performed with the use of baseline data from 3 randomized controlled trials in Army, Air Force, and Marine recruits ( n = 401; 179 men, 222 women). Dietary intake was estimated from a food-frequency questionnaire. A dietary pattern characterized by calcium, potassium, and protein was derived via reduced rank regression and a pattern z score was computed for each volunteer, where higher scores indicated greater adherence to the pattern. At the 4% (metaphysis) and 14% (diaphysis) sites of the tibia, bone mineral content (BMC), volumetric bone mineral density, robustness, and strength indexes were evaluated. Associations between dietary pattern z score as the predictor variable and bone indexes as the response variables were evaluated by multiple linear regression. Results: Pattern z score was positively associated with BMC ( P = 0.004) and strength ( P = 0.01) at the metaphysis and with BMC ( P = 0.0002), strength ( P = 0.0006), and robustness ( P = 0.02) at the diaphysis when controlling for age, sex, race, energy, smoking, education, and exercise. Further adjustment for BMI attenuated the associations, except with diaphyseal BMC ( P = 0.005) and strength ( P = 0.01). When height and weight were used in place of body mass index, the association with BMC remained ( P = 0.046). Conclusions: A dietary pattern rich in calcium, potassium, and protein is positively associated with measures of tibia BMC and strength in recruits entering IMT. Whether adherence to this dietary pattern before IMT affects injury susceptibility during training remains to be determined. These trials were registered at clinicaltrials.gov as NCT01617109 and NCT02636348.